NMR of drugs and ligands bound to membrane receptors. - Watts, A (1999)
NMR methods are now able to give detailed structural, dynamic and electronic information about drugs and ligands while constrained at their site of action in membrane-embedded receptors, information which is essential for mechanistic descriptions of their action and design of new ligands. Using solid state NMR methods, a peptic ulcer drug analogue has been described at atomic resolution (to +/- 0.3 A between two atoms) at its site of action in the gastric H+/K+-ATPase, and the aromaticity of the agonist binding site of the nicotinic acetylcholine receptor has been demonstrated, with both targets in functionally competent membranes under conditions similar to those used in screening assays. G-protein-coupled receptor ligands and prosthetic groups are also being resolved using NMR methods.